Pedagog – mistrz czy artysta? - Bogus-Spyra, Marzena (Instytut Sztuk Pięknych Uniwersytetu Rzeszowskiego, 2021)
The repeated question about who is my master has provoked me into giving a nonconforming answer, or anyway, not entirely in keeping with the “fundamental” model of education based on the master-disciple principle. I think this relationship is not a sine qua non in contemporary education, which is, indeed, based on post-figurative culture, yet increasingly co-figurative and pre-figurative. It is a cliché to repeat that not all scholars can be masters and not all teachers deserve this name. The name itself raises objections: “master” suggests superiority and therefore power over someone. Master, according to a centuries-old tradition, expects a long apprenticeship, which in the current process of education is not always liberating, just the opposite, it can be a hindrance, threatening an individual’s independence, intimidating and requiring subservience towards the professed values. Why not search for other ideals, instead of a master? Search for a scholar? As Barbara Skarga said, only reason should have authority! That is why I would like “master” to be replaced by “artist”, because artist has doubts and tries things out; has flashes of inspirations but is always on the lookout for novelty, without claiming to know all.
Teacher – master or artist?
Keywords: pedagog; mistrz; artysta; relacja; teacher; master; artist; relationship